Collaborative product development: The case of network operators - Robin Häberle; Nico Grove (International Telecommunications Society (ITS), 2012)
The goal of this paper is to evaluate the importance of cloud services for Integrated Service Providers and how collaborative product development could strengthen their position within the Cloud Industry. The global cloud market is growing rapidly and gaining daily more momentum. The German Bitkom estimates B2B cloud revenues to exceed 10 bn Euro in Germany by 2016, five times its revenue in 2011. Telecommunication Services - home market to Integrated Service Providers (ISPs) - on the contrary are mostly past their booming years. Even so ISPs are playing a crucial part in the cloud - basically connecting production and consumption - they are typically not mentioned amongst the main Cloud providers. This is puzzling as an integrated network is able to deliver significant unique value in areas such as SLA management, locality, security and inter-cloud connectivity.
Keywords: 330; Integrated Service Provider; Network Operator; Cloud Services; Product Development; Cloud Value Chain